Eyes On The Prize - Henry Hampton (USA Blackside, 1990)
This is a documentary series about the glory years of the American Civil Rights Movement, starting in 1952 with the murder of Emmit Till and the subsequent trial and ending with the civil rights march to Selma in 1965. Along the way, the series touches on the major figures of the movement such as Martin Luther King and Rosa Parks and major incidents such as the Little Rock school riots and Montgomery, Alabama Transit Boycott.
Language:Englısh Subtitles:No Subtitle
Keywords: History; Documentary